2011
DOI: 10.1017/s0960258511000274
|View full text |Cite
|
Sign up to set email alerts
|

A fast ethanol assay to detect seed deterioration

Abstract: The most common way to test seed quality is to use a simple and reliable but time-and space-consuming germination test. In this paper we present a fast and simple method to analyse cabbage seed deterioration by measuring ethanol production from partially imbibed seeds. The method uses a modified breath analyser and is simple compared to gas chromatographic or enzymatic procedures. A modified method using elevated temperatures (408C instead of 208C) shortened the assay time and improved its sensitivity. The ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 28 publications
(35 reference statements)
3
37
0
5
Order By: Relevance
“…Mendes et al (2009) and Aumonde et al (2012) On the other hand, Crispin et al (1994), Buckley and Huang (2011) and Kodde et al (2012) reported the opposite trend in seeds of G. max, B. napus and Brassica oleracea L. respectively with the use of titration or by gas chromatography. The difference in results may result from incubation temperature.…”
Section: Lotsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mendes et al (2009) and Aumonde et al (2012) On the other hand, Crispin et al (1994), Buckley and Huang (2011) and Kodde et al (2012) reported the opposite trend in seeds of G. max, B. napus and Brassica oleracea L. respectively with the use of titration or by gas chromatography. The difference in results may result from incubation temperature.…”
Section: Lotsmentioning
confidence: 99%
“…Seed performance in the field is a complex characteristic related to the environmental, physiological and genetic aspects of seeds which cannot be measured in a single location or with few replications (MARCOS-FILHO, 2005;KODDE et al, 2012).…”
Section: Lotsmentioning
confidence: 99%
“…(CGR): 100 × GR/FGP, where FGP corresponds to the final GP (Dewir et al 2011) and T 50 : number of days at which the seeds attained 50 % of their final GP (Kodde et al 2012).…”
Section: The Test Duration Was 60 Daysmentioning
confidence: 99%
“…However, deterioration occurs in the process of seeds storage, which causes a drop of seed vigor, poor seedling emergence and bad influence on intracellular physiological reactions (McDonald, 1999;Kapoor et al, 2011). Although the exact mechanisms of seed vigour losing are still under research, the lipid peroxidation has been considered as the main explanation for seed deterioration due to accumulation of reactive oxygen species (ROS) (Bailly et al, 2008;Kodde et al, 2012). Furthermore, deterioration is related to loss of membrane integrity, cell structural disruptions and other various cellular changes such as DNA degradation, protein denaturation and ultimately causes cell death (McDonald, 1999;Karuppanapandian et al, 2011).…”
Section: Introductionmentioning
confidence: 99%